Basic algebraic topology - Shastri, Anant R. (CRC Press, 2014)
"Thoroughly classroom-tested, this self-contained text teaches algebraic topology to students at the MSc and PhD levels, taking them all the way to becoming algebraic topologists. Requiring basic training in point set topology, linear algebra, and group theory, the book includes historical remarks to make the subject more meaningful to students. Also suitable for researchers, it provides references for further reading, presents full proofs of all results, and includes numerous exercises"--